Synchronous and Metachronous Breast and Ovarian Cancer: Experience From Two Large Cancer Center - Tasca, Giulia; Dieci, Maria Vittoria; Baretta, Zora; Faggioni, Giovanni; Montagna, Marco; Nicoletto, Maria Ornella; Peccatori, Fedro Alessandro; Guarneri, Valentina; Colombo, Nicoletta (Frontiers in Oncology, 2020)
Purpose We aimed to evaluate the clinico-pathological characteristics and survival outcomes of patients with synchronous or metachronous breast cancer (BC) and ovarian cancer (OC). Materials and Methods Patients with synchronous or metachronous BC and OC were retrospectively identified at two large cancer centers. Clinico-pahological characteristics, BRCA1/2 status and follow up data were gathered. Patients were classified according to the first cancer diagnosis in the following groups: Breast Cancer first, Ovarian Cancer first, Synchronous Breast and Ovarian Cancer. Overall survival (OS) was calculated as the time interval between each cancer diagnosis to death or last follow up. Results Overall, 270 patients were included: n= 194 (72%) in BC first group, n= 51 (19%) in OC first, and n= 25 (9%) in synchronous. BRCA status was available for 182 (67.4%) patients and 112 (62%) harbored pathogenetic mutations. BC first group included more frequently patients with BRCA mutation, triple negative BC phenotype and more aggressive OC features. Median time between the two diagnosis was longer in BC first group vs OC first group (95 vs 68 months, p=0.021). A total of 105 OS events occurred, mostly related to OC (70.5%). We observed no differences in terms of OS according to the first cancer diagnosis. Age >50 years and advanced OC stage were negative independent prognostic factors for OS from the first diagnosis. Conclusions In this cohort of patients with BC and OC, survival was dominated by OC related mortality. These data may be useful to plan and carry out adequate and timely surveillance programs and preventive measures.